Evaluation of microbial contamination of mobile phones and computer mice and keyboards in a dental school - Taraneh Movahhed; Mahboobe Dehghani; Tayyebeh Ghoddusi (Mashhad University of Medical Sciences, 2018)
Introduction: Mobile phones and computers are a reservoir of growth and transmission of microorganisms. This study aimed to evaluate the microbial contamination of computers and mobile phones used by students of an academic dental school, compared to the students of a non-medical school. Methods: Sampling was performed on 44 computers and 45 mobile phones in a dental school (test) and a non-medical school (control). Samples were obtained from the Enter and Backspace keys of keyboards, the left-click button of computer mice and touch-screen of mobile phones. Afterwards, the samples were cultured, followed by colony count. Results: The most frequently detected microbes were coagulase-negative Staphylococci, Bacillus and Micrococcus. In computer samples, pathogenic bacteria including Staphylococcus aureus and Klebsiella, were found only in the samples of the dental school. Staphylococcus aureus and Micrococcus were significantly more prevalent in the test group. Microorganisms belonging to human normal flora (e.g., Bacillus, Entrococcus, Corynebacterium, and Tetragenococcus) were significantly more prevalent in computers of the control group. In terms of the frequency of pathogenic bacteria found on mobile phones, no significant difference was observed between the study groups. Conclusion: The prevalence of normal human flora was higher in the control group (non-medical) relative to the test group (dental). Meanwhile, pathogenic bacteria were more prevalent in the samples of the dental school. Also, computers were more contaminated than mobile phones. Hygiene promotion programs should be implemented in both dental and non-medical schools.